Graphene-diamond junction photoemission microscopy and electronic interactions. (23rd July 2020) - Wan, Gary; Panditharatne, Sanjeevani; Fox, Neil A; Cattelan, Mattia
Abstract: Polycrystalline graphene was transferred onto differently terminated epitaxial layers of boron-doped diamond deposited onto single crystal substrates. Chemical and electronic characterisation was performed using energy-filtered photoemission electron microscopy and angle-resolved photoemission spectroscopy. Electronic interaction between the diamond and graphene was observed, where doping of the graphene on the hydrogen and oxygen terminated diamond was n-doping of 250 meV and 0 meV respectively. We found that the wide window of achievable graphene doping is effectively determined by the diamond surface dipole, easily tuneable with a varying surface functionalisation. A Schottky junction using the graphene-diamond structure was clearly observed and shown to reduce downward band bending of the hydrogen terminated diamond, producing a Schottky barrier height of 330 meV.